HnRNP‐A1 binds to the IRES of MELOE‐1 antigen to promote MELOE‐1 translation in stressed melanoma cells. Issue 3 (12th September 2021) - Charpentier, Maud; Dupré, Emilie; Fortun, Agnès; Briand, Floriane; Maillasson, Mike; Com, Emmanuelle; Pineau, Charles; Labarrière, Nathalie; Rabu, Catherine; Lang, François
Abstract : The major challenge in antigen‐specific immunotherapy of cancer is to select the most relevant tumor antigens to target. To this aim, understanding their mode of expression by tumor cells is critical. We previously identified a melanoma‐specific antigen, melanoma‐overexpressed antigen 1 (MELOE‐1)—coded for by a long noncoding RNA—whose internal ribosomal entry sequence (IRES)‐dependent translation is restricted to tumor cells. This restricted expression is associated with the presence of a broad‐specific T‐cell repertoire that is involved in tumor immunosurveillance in melanoma patients. In the present work, we explored the translation control of MELOE‐1 and provide evidence that heterogeneous nuclear ribonucleoprotein A1 (hnRNP‐A1) binds to the MELOE‐1 IRES and acts as an IRES trans‐activating factor (ITAF) to promote the translation of MELOE‐1 in melanoma cells. In addition, we showed that endoplasmic reticulum (ER) stress induced by thapsigargin, which promotes hnRNP‐A1 cytoplasmic translocation, enhances MELOE‐1 translation and recognition of melanoma cells by a MELOE‐1‐specific T‐cell clone. These findings suggest that pharmacological stimulation of stress pathways may enhance the efficacy of immunotherapies targeting stress‐induced tumor antigens such as MELOE‐1. Abstract : Our study demonstrates that reticular stress in melanoma cells promoted the translocation of the IRES transacting factor hnRPN‐A1 to the cytoplasm. By binding to the IRES site of meloe mRNA, hnRPN‐A1 promoted the translation of the melanoma‐specific antigen MELOE‐1 and led to the expression of a new immunogenic HLA/peptide complex at the cell surface. Altogether, our data suggest that pharmacological stimulation of stress pathways may enhance the efficacy of T‐cell based immunotherapies in targeting stress‐induced tumor antigens, such as MELOE‐1 in patients with melanoma.